PENGARUH MEDIA MIND MAPPING TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI TK IT ANNISA PEKANBARU - Reni Novita Sari; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The Research in TK IT ANNISA Pekanbaru consisting of 24 children there are problems as follows: that there are still children who are not able to (1) Mention and distinguish words that have the same prefix and suffix are the same, (2) Connecting article simple drawing, (3) Reading the corresponding images or symbols that denote it. The purpose of this study was to determine the ability to read the beginning of children aged 5-6 years in TK IT ANNISA Pekanbaru, before the application of media mind mapping, to determine the ability to read the beginning of children aged 5-6 years in TK IT ANNISA Pekanbaru, after application of mind mapping media. The number of samples in the study were as many as 24 people kindergartner B. This study is an experiment that uses one grou desaian pretest and posttest design through observation sheet. In this study, the ability to read the beginning of children aged 5-6 years before using mind mapping media that are in the high category rang from 0 or 0%, the categories were as many as 17 people or 71% and the low category as many as 7 people or 29%. And after using mind mapping media, there are 18 children in the high category with a percentage of 75%, 5 children medium category with a percentage of 21% and 1 child lower category with the percentage of 4%. And in this study Early reading ability of children according to the indicator reading skills of children aged 5-6 years that the reading ability of the highest in the indicator reading the name itself that before the use of media mind mapping of 94.79%, after the media use mind mapping percentage turn out to be 96.00%. From the analysis daa research results we can conclude that Ha is accepted and H0 result t = 10.312 and t table of 23 on a standard error of 0.05 so that t table = 2,09 (10.312> 2.09) with demikan found influence significantly to the reading skills of children aged 5-6 years after using mind mapping media.Keywords: Effects of Media Mind Mapping, Literacy Starters